Object Based Analysis of Remote Sensing Images (International Journal of Innovative Research in Computer Science & Technology, 2022)
Remote sensing is the process of detecting  and identifying a region's physical properties by assessing  reflected but also transmitted radiation from a range.  Analog pictures include aerial photography, whereas  digital images include satellite images taken using  electronic sensors. A digital picture is made up of pixels  that are arranged in a two-dimensional array. Pixel-based  categorization algorithms were less successful as spatial  resolution increased, since the connection among pixel size  as well as the dimension of observable elements on the  Planet's surface altered dramatically. In this paper the  author discussed about image analysis based on objects  and also characterized OBIA and GOBIA formation and  its analysis. The chief objective of this paper is to gives a  brief overview the technology that has been proved very  efficient in analyzing the satellite (VHR) images. The  study's future scope is as follows: The globe has seen  extraordinary and quick progress in the fields of remote  sensing, geospatial data collecting, and mapping during the  previous several decades. The technology is gaining  traction in terms of its use and application in several  sectors.
Keywords: Image processing; Image Analysis; Landsat; Objects; OBIA and GEOBIA; Remote Sensing